Zbirka rešenih izpitnih nalog pri predmetu Verjetnost - Kelenc, Aleksander (University of Maribor Press, 2025)
Collection of Solved Exam Problems in Probability. This collection of solved exam problems is primarily intended for third-year students of the university study programs Electrical Engineering and Computer Science and Information Technologies at UM FERI, where Probability is offered as an elective course. However, the collection will also be useful for other students who encounter probability concepts in their studies. The first chapter of the collection contains past exam problems, while the second provides their solutions along with selected problem-solving procedures. Successfully solving these problems requires at least a basic understanding of combinatorics and probability. The topics covered in this collection include geometric probability, conditional and total probability, discrete and continuous random variables, discrete random vectors, and the fundamentals of statistics.